Penentuan Status Mutu Air Tukad Mati Dari Kuta Utara Hingga Kuta Selatan Berdasarkan Metode Indeks Pencemaran - I Kadek Widiantara; Pramana Eka Putra (Program Studi Teknik Lingkungan Unmas Denpasar, 2022)
This study discusses the water quality of Tukad Mati which occupies the area of Badung Regency in the upstream and downstream parts that stretch from North Kuta to South Kuta while the middle part crosses Denpasar City in terms of physical, chemical, and biological parameters and classifies the water quality of Tukad Mati with the Pollution Index method. The purpose of this study was to determine the quality of Tukad Mati water in terms of several parameters such as temperature, dissolved residue, suspended solids, pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), phosphate, fecal coliform, and total coliform. The results of the measurement of water samples are compared with environmental quality standards and environmental damage standard criteria based on Bali Governor Regulation No. 16 of 2016. The results of the analysis show that there are several parameters whose values exceed the threshold of class II water quality standards, namely TSS, BOD, and phosphate. The result of the Tukad Mati Pollution Index value in the upstream area has a value of 4.86 in the middle has a value of 3.02 and downstream has a value of 3.48 which is categorized as lightly polluted.